Športna rekreacija na fakulteti za šport in njeni odmevi v slovenskem športnem in družbenem prostoru - Berčič, Herman (Šport (Ljubljana), 2023)
Sport recreation at the Faculty of Sport was founded as a study programme in which students (we) learnt about the individual formative seg- ments of this sport variant through pedagogical, professional and research work. The development of sport recreation has followed the develop- ment of the wider socio-economic environment and the narrower sport domains, and has also been based on the findings of some other profes- sional and scientific disciplines. Within the framework of the internal division, the whole structure of the population in the living environment and all its components, in particular the family, the age of maturity and the elderly, have been studied. The work environment was specifically examined, with its many organisational and contextual forms of sport recreation, which have been implemented in a number of work organisa- tions or companies. Consideration of sport recreation in relation to tourism has fostered its development and contributed to the enrichment of the content of sport in tourism. Systematic scientific research work has enriched the entire field, and many graduates have raised the level of awareness and the sports culture of the Slovenian population.
Keywords: bivalno okolje; delovno okolje; raziskovalna dejavnost; razvoj; šport; športna rekreacija; turizem